What Are the Stages of the Creative Process? What Visual Art Students Are Saying. - Botella, Marion; Zenasni, Franck; Lubart, Todd (Frontiers in Psychology, 2018)
A number of models of both artistic and creative processes exist. However these models diverge in terms of the number of stages described and their sequences. Thus, a model presents usually between 4 and 9 stages which may comprise substages. Although some of these stages may refer to the same phenomena, they may be designated by very different terms. These differences in modeling reflect divergences in the methodology used (interviews or case studies) but also in the populations studied (artists, scientists, writers, etc.) Yet, the models constructed with reference to a specific creative domain can not necessarily be fully generalized and apply to all creative domains. It is therefore worthwhile to develop the description of models of the creative process by targeting a specific domains or a specific population. The objective of this study is to propose a complete list of the stages of the visual artistic creative process in order to integrate them in the Creative process Report Diary (CRD; Botella, Nelson & Zenasni, 2017). This tool allows self-observations of the creative process in real situations by presenting a list of stages of the process. In the present study, 28 art students were interviewed in order to identify the specific stages of their process of visual artistic creativity. Results of our analyses highlight 17 distinct stages in the students’ processes of visual artistic creation. Although some of these may correspond to stages already identified in the literature, others are new. No existing model includes all of these stages. Implications of using this expanded set of stages are discussed according to the CRD.